Cover Image, Volume 30, Issue 6. Issue 6 (8th June 2020) - Görler, Richard; Wiskott, Laurenz; Cheng, Sen
Abstract : Cover legend: The cover image is based on the Research Article Improving sensory representations using episodic memory by Richard Görler et al, https://doi.org/10.1002/hipo.23186 .